PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA MANGUTAMA BADUNG TAHUN 2017 - Putri Apsari, Ni Made Dwi (CITIZEN CHARTER, 2017)
PDAM is a regional company that has authority in providing clean water consumption for the community. Municipal Waterworks (PDAM) of Tirta Mangutama is one of the agencies that often get complaints from customers regarding its services. Some causes of lack’s service of PDAM Tirta Mangutama were the increasing of water losses from community fraud, pipeline leakage, and network damage. The phenomenon occurs related to the problems and complaints of water distribution, it still got responses from the customers of PDAM’s Tirta Mangutama Badung. This research was included in associative research with quantitative approach. It was involving 100 customers of Municipal Waterworks’ Tirta Mangutama Badung as the respondents. The indicators in the study were tested using validity and reliability test. The tests of hypotheses was using simple linear analysis. The results showed that the quality of service that includes tangible, reliability, responsiveness, assurance and empathy have a positive and significant impact on customer satisfaction. R Square showed the result of 0.613 means customer satisfaction was influenced by service quality which was 61.3%, while the rest was 38.7% in this research model is explained by other factors. Keywords : Service quality, customer satisfaction, municipal waterworks